Construct, Convergent, and Discriminant Validity of the Beach Center Family Quality of Life Scale for Singapore. Issue 3 (July 2019) - Waschl, Nicolette; Xie, Huichao; Chen, Mo; Poon, Kenneth K.
Abstract : Family quality of life (FQoL) constitutes an important aspect of early intervention. However, the culture bound nature of this construct necessitates validation of FQoL measures when being used in a culture different from the one in which they were developed. This study sought to understand the psychometric properties and construct validity of the Beach Center FQoL (BCFQoL) scale in Singapore. Data from 307 caregivers of children in an early intervention program were used. These caregivers completed the BCFQoL scale and external validity measures of family outcomes, psychological distress, and life situation. Confirmatory factor analysis and correlations were used to examine the factor structure and convergent and discriminant validity of the BCFQoL scale. Results indicated support for 5 FQoL dimensions and a higher-order FQoL factor. External convergent and discriminant validity, as well as internal statistical discriminant validity of the individual BCFQoL dimensions were supported. Despite evidence of internal statistical discriminant validity, there was little variation in the strength of the relationships between individual BCFQoL dimensions and the various external validity measures. Overall, the results of this study support the use of the BCFQoL scale as a valid measure of FQoL in Singapore.